#TITLE_ALTERNATIVE# - DARMANSYAH (NIM : 13606039); Dosen Pembimbing : Dr. Ir. M.Giri Suada; Dr.Ir. Leonardo Gunawan, ANGGI
The need of oil in the world is now quite high. This condition can trigger the massive exploration of the oil in the deepwater sea. Of course, the pipe that carry up oil can be longer and heavier. When it happen, the presence of the aircan can help in reducing the stress due to riserÃ‚Â’s weight. The Aim of the project which is done here is to analyse the effect of aircan addition for top tension riser configuration. The data of the riser is obtained from UNOCAL which is used as preliminary study of top tension riser with additional aircan. The model of riser is done by using finite element method to get dynamics properties of riser. this process is usually called modal analysis. The result of modal analysis is natural frequency and modes shapes. This dynamics properties will be an input to get the response of vortex induced vibration. The interaction of vortex induced vibration is got by inputing the current profile. The interaction between current profile and dynamics properties will produce excited and dominant modes. From that interaction, stress occurred along the riser can be known. Stress distribution is used to search the point or place which have high damage rate. This means that fatique life of riser locally can be predicted and anticipated. Fatique life is calculated by imputing S-N Curve for each material.